2- Population Projections for Malawi and its Regions, 1998-2023 - Palamuleni, Martin E. (African Sociological Review, 2007)
The main objective of this paper is to critically evaluate the most recent projections prepared by the National Statistical Office (NSO) and provide alternative projections for Malawi. The Epidemic Projection Package (EPP) developed by UNAIDS and the SPECTRUM programme developed by the Futures Group were used to model the Malawian HIV epidemic, to project future trends in HIV/AIDS and population and to estimate the demographic impact of AIDS. The national HIV prevalence surveys among pregnant women from 1985 to 2000 served as the data sets used to calibrate the input HIV prevalence values for the model, while demographic data obtained from the 1998 Malawi Population and Housing Census acted as a base for population projections. The results indicate that the population of Malawi will continue to grow despite the negative impact of HIV/AIDS epidemic. The population of Malawi is expected to increase from 9.92 million in 1998 to 13.52 in 2010 and to 16.84 million in 2020. The population projections presented in this study are not about predicting the future so much as they are about exploring the consequences of today’s trends. These are intended to show what the future will look like if today’s trends continue for the next decade or two. As in the case of Malawi, the predicted future is sufficiently undesirable that it should serve to focus our attention on implementing programmes today that will protect people fromHIVinfection and promise a brighter future.